Expression pattern of perilipins in human brain during aging and in Alzheimer's disease. (5th August 2021) - Conte, Maria; Medici, Valentina; Malagoli, Davide; Chiariello, Antonio; Cirrincione, Alice; Davin, Annalisa; Chikhladze, Maia; Vasuri, Francesco; Legname, Giuseppe; Ferrer, Isidre; Vanni, Silvia; Marcon, Gabriella; et al.
Abstract: Aims: Perilipins are conserved proteins that decorate intracellular lipid droplets and are essential for lipid metabolism. To date, there is limited knowledge on their expression in human brain or their involvement in brain aging and neurodegeneration. The aim of this study was to characterise the expression levels of perilipins (Plin1–Plin5) in different cerebral areas from subjects of different age, with or without signs of neurodegeneration. Methods: We performed real‐time RT‐PCR, western blotting, immunohistochemistry and confocal microscopy analyses in autoptic brain samples of frontal and temporal cortex, cerebellum and hippocampus from subjects ranging from 33 to 104 years of age, with or without histological signs of neurodegeneration. To test the possible relationship between Plins and inflammation, correlation analysis with IL‐6 expression was also performed. Results: Plin2, Plin3 and Plin5, but not Plin1 and Plin4, are expressed in the considered brain areas with different intensities. Plin2 appears to be expressed more in grey matter, particularly in neurons in all the areas analysed, whereas Plin3 and Plin5 appear to be expressed more in white matter. Plin3 seems to be expressed more in astrocytes. Only Plin2 expression is higher in old subjects and patients with early tauopathy or Alzheimer's disease and is associated with IL‐6 expression. Conclusions: Perilipins are expressed in human brain but only Plin2 appears to be modulated with age and neurodegeneration and linked to an inflammatory state. We propose that the accumulation of lipid droplets decorated with Plin2 occurs during brain aging and that this accumulation may be an early marker and initial step of inflammation and neurodegeneration. Abstract : Perilipins (Plins) are a family of proteins decorating intracellular lipid droplets. Their expression was investigated in human brain autoptic samples. Plin2, Plin3 and Plin5, but not Plin1 and Plin4, are expressed in all areas investigated, though with different intensity and in different cell types. Plin2 expression is higher in neurons from old healthy subjects compared with adult and seems to be particularly prominent in neurons from patients with neurodegenerative diseases compared with healthy elderly and centenarians.